Low Energy Electron Induced Reactions in Condensed Methanol. (August 2015) - Kundu, Sramana; Davis, Daly; Prabhudesai, Vaibhav S; Krishnakumar, E
Synopsis: Resonant formation of H - and O - ions and formation of ethylene glycol (OHCH2 CH2 OH) on electron impact is seen in the same energy range in condensed molecular films of methanol (CH3 OH). This could indicate a new reaction pathway involving bond breaking and bond formation at specific electron energies in condensed methanol.